Economic Performance of Enterprises Promoted under ARYA and Relationship with Entrepreneurial Competencies - Chandre Gowda, M. J.; Rana, Rajesh Kumar; Pal, Partha Prathim; Dubey, Shantanu Kumar; Kumar, Amrendra; Meena, Mohar; Singh, Randhir; Bordoloi, Rajumoni; A, Bhaskaran; A. A., Raut; T., Rajesh; Kumar, Bagish; et al. (Indian Journal of Extension Education, 2023)
Attracting and rural youth in agriculture (ARYA) is a national programme of Indian Council of Agricultural Research implemented through Krishi Vigyan Kendras (KVKs) since 2016-17. The current investigation was carried out in 2021-22 with a total of 684 rural youth randomly identified from among the functional units under various enterprises. Among the nine major enterprises promoted under ARYA, performance of poultry units were better in terms of operational duration and total turnover per enterprise despite incurring the higher expenditure. Nursery enterprises showed the highest net income per unit and also created maximum assets. On the other hand, the benefit-cost ratio was higher in piggery enterprises and per day net income was highest in processing and value-addition units. More employment generation was recorded in fish and goat farming enterprises. The results proved that each of the agribusiness areas has strengths on different parameters. Besides the choice of enterprises that are locally viable, the entrepreneurial competency of the entrepreneurs was essential to sustain the enterprises. Successful entrepreneurship promotion has the possibility for attracting and retaining youth in rural areas through technology-supported agribusiness development.